HISTÓRIA EVOLUTIVA DA BACIA DO PRATA: UMA ABORDAGEM NA CONSERVAÇÃO DE ESPÉCIES ARBÓREAS - FARIAS, Ivan Justino,; PONTARA, Vanessa,; CURIEL, Matheus Henrique,; GUIMARÃES, Felipe da Silva,; SANTOS, Elizandra Lima dos,; BUENO, Marcelo Leandro, (ANAIS DO ENIC, 2022)
-